Code-switching e footing para a construção do humor : estudo de caso da sitcom "Friends" - Broilo Neto, Gilberto (My University, 2017)
This dissertation is about code-switching and footing in the north-american sitcom Friends. Both the switch of language and the identity positioning are objects of analysis for the Interactional Sociolinguistics area (GOFFMAN, 1981; HUDSON, 1996; DURANTI, 1997), which is the main theory of this investigation. Not only theoretical aspects of this background are used but also studies about humour (RASKIN, 1979; WRIGHT, 1875), sitcom (FURQUIM, 1999; SAVORELLI, 2010; VANDAELE, 1996), multimodalidality (GOODWIN, 2010; KRESS; LEEUWEN, 1996; VIEIRA; SILVESTRE, 2015), estereotypes (LAKOFF, 1987; SCHIAPPA; GREGG; HEWES, 2005), performance (TURNER, 1987), social generalization (BLUM, 2004), among others. In order to solve the problem of this research, which resides in understanding whether both code-switching and footing are strategies of humour in the sitcom Friends, we opted for the case study of this situational comedy and for the investigation of the communicative acts in which the switch of linguistic codes and identity repositiong are found. The general objective of this research is to examine the connection between humour creation and the situations in which there is evidence of code-switching between American English and British English, positioning between American English varieties and the multimodal positioning of communicative interactions in episodes of the sitcom Friends. The specific objectives are (a) to identify the constructs of cultural identity in the sitcom Friends, (b) to identify the situations of code-switching in the humour generation, (c) to analyse the situations of code-switching and the multimodal aspects of the communicative act and (d) to analyse the effects of humour, highlighting the intervenient cultural aspects related to such effects. In order to fulfill these objectives, we, also, based our research on the studies of framing (GOFFMAN, 1974), which are identified in the scenes of code-switching and footing, being transcribed according to the Conversation Analysis symbolic conventions (SACKS; SCHEGLOFF; JEFFERSON, 1974). The results show that, in the episodes of the series Friends analysed, both code-switching and footing are potential strategic mecanisms to create humour formed in several situations through different comical functions, such as: cultural satire, stereotyped caricature, reality representation, among others.
Esta dissertação trata de code-switching e footing na sitcom estadunidense Friends. Tanto a troca linguística como o posicionamento identitário são elementos de análise da Sociolinguística Interacional (GOFFMAN, 1981; HUDSON, 1996; DURANTI, 1997), que é a teoria basilar desta investigação. Não somente aspectos teóricos desse arcabouço são utilizados como também estudos sobre humor (RASKIN, 1979; WRIGHT, 1875), sitcom (FURQUIM, 1999; SAVORELLI, 2010; VANDAELE, 1996), multimodalidade (GOODWIN, 2010; KRESS; LEEUWEN, 1996; VIEIRA; SILVESTRE, 2015), estereótipos (LAKOFF, 1987; SCHIAPPA; GREGG; HEWES, 2005), performance (TURNER, 1987), generalização social (BLUM, 2004), dentre outros. A fim de responder ao problema desta pesquisa, que reside em entender se o code-switching e o footing são mecanismos de geração do humor na sitcom Friends, optamos pelo estudo de caso dessa comédia seriada e pela investigação dos atos comunicativos em que se fazem presentes a alternância de código linguístico e o reposicionamento identitário. O objetivo geral da pesquisa é examinar a relação entre a geração de humor e as situações em que há a presença de code-switching entre Inglês Americano e do Inglês Britânico e de posicionamento entre variedades do Inglês Americano, além de considerar o posicionamento multimodal das interações comunicativas em episódios da sitcom Friends. Os objetivos específicos são (a) identificar os construtos identitários culturais na sitcom Friends, (b) identificar as situações de code-switching na geração de humor, (c) analisar situações de code-switching e aspectos multimodais na interação comunicativa e (d) analisar os efeitos do humor, com ênfase em fatores culturais intervenientes. Com a finalidade de cumprir com esses objetivos, alicerçamos nossa pesquisa, também, nos estudos de framing (GOFFMAN, 1974), que foram identificados nas cenas em que há code-switching e footing, que foram transcritas a partir da simbologia da Análise da Conversa (SACKS; SCHEGLOFF; JEFFERSON, 1974). Os resultados demonstram que, nos episódios da série Friends que foram analisados, o code-switching e o footing são mecanismos potenciais estratégicos de geração de humor que se formam em situações plurais com diversas funções de comicidade, tais como: sátira cultural, caricaturização estereotipada, representação da realidade, dentre outras.
Keywords: Friends (Programa de televisão); Linguagem e línguas -- Variação; Diglossia (Linguística); Bilinguismo; Linguística aplicada; Friends (TV program); Language and languages - Variation; Diglossia (Linguistics); Bilingualism